EXPLORING THE ESSENCE OF LOGICAL POSITIVISM: UNVEILING ITS IMPACT ON THE LANDSCAPE OF PHILOSOPHICAL DISCOURSE - AHMAD ARIFIN; Rini, Setia (Al Qolam University, 2024)
The passage transitions to a research exploration, emphasizing the philosophical stream of positivism, its connection with scientific knowledge, and its impact on education. The research methodology is outlined, specifying aqualitative approach through literature review analysis. The historical section delves into logical positivism, its origins, and its influence within the Vienna Circle. The rejection of metaphysics, the classification of statements, and the pursuit ofa universal scientific language are highlighted. The role of philosophy in logical positivism is presented as a logical-linguistic activity aimed at clarifying scientific propositions. Keywords: Intertwined, Historical, Logic, Positivism, Philosophy, Impact